2016
DOI: 10.1016/j.diabres.2016.09.026
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of fasting hyperglycemia to changes in fat and muscle mass after exercise training in type 2 diabetes

Abstract: Aims Exercise training (ET) has been variably associated with body composition changes among persons with type 2 diabetes (T2DM). The degree to which these changes are related to hyperglycemia remains unclear. Our objective was to investigate the relationship of baseline fasting glucose (FG) to the magnitude of muscle gains and fat loss after ET in individuals with T2DM. Methods Participants were enrolled in the SHAPE-2 trial, a six month supervised aerobic and resistance training intervention (three days/we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…As in other murine models of altered metabolism [30, 31], this could contribute to insulin resistance in skeletal muscle, as manifested by glucose intolerance and underlined by reduced insulin-stimulated Akt phosphorylation, a key mediator of glucose uptake [32]. Glucose uptake in skeletal muscle becomes limited in parallel to an age-dependent reduction in metabolically active lean mass and an increase in visceral obesity [33]. Consistent with this, lean mass decreased reciprocally to the increase in fat mass in older Cc2 −/− male mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other murine models of altered metabolism [30, 31], this could contribute to insulin resistance in skeletal muscle, as manifested by glucose intolerance and underlined by reduced insulin-stimulated Akt phosphorylation, a key mediator of glucose uptake [32]. Glucose uptake in skeletal muscle becomes limited in parallel to an age-dependent reduction in metabolically active lean mass and an increase in visceral obesity [33]. Consistent with this, lean mass decreased reciprocally to the increase in fat mass in older Cc2 −/− male mice.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas age-related hyperinsulinaemia, insulin resistance and visceral obesity [4143] are commonly associated with reduced glucose uptake in skeletal muscle in parallel with a reduction in metabolically active lean mass [33], decreased fenestration in the liver sinusoidal endothelium and other structural changes that reduce insulin uptake by hepatocytes, and hence reduce insulin clearance, have recently emerged as mechanisms underlying age-related hyperinsulinaemia and insulin resistance [44]. The current study provides an alternative mechanism of hyperinsulinaemia in older Cc2 −/− male mutant mice, implicating a progressive reduction in hepatic CEACAM1-mediated insulin clearance that fails to counter persistent GLP-1-mediated release of insulin in older mutant mice.…”
Section: Discussionmentioning
confidence: 99%
“…After AE and RT interventions, participants presented total fat mass decreased and total lean body mass increased in association of fasting glucose reduction. So, these data demonstrate that muscle gain and fat loss after ET are positively related to baseline hyperglycemia [20].…”
Section: Discussionmentioning
confidence: 70%
“…However, [19] highlighted some limitations, as sample size and subjectivity on physical function measurement [19]. In a contribution to this findings, [20] performed supervised aerobic and resistance training intervention for 6 months in 50 individuals with DM2. After AE and RT interventions, participants presented total fat mass decreased and total lean body mass increased in association of fasting glucose reduction.…”
Section: Discussionmentioning
confidence: 99%
“…5 Lean body mass is the primary site of glucose uptake 8 ; and therefore, it has been suggested that LBM protects against cardio-metabolic risk factors and diabetes. 9,10 Although rational, few studies support that both BMI and high-LBM are independently associated with unfavorable cardio-metabolic profiles. 5,11 For example, a study including 421 men and women suggests that age and LBM (but not fat mass) explained 46% of the unfavorable cardio-metabolic risk factors profile.…”
Section: Introductionmentioning
confidence: 99%